The Influence of Leadership and Organizational Culture on Employee Performance - Yuliaty, Farida; Firmansyah, M.Lutfi (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the influence of leadership and organizational culture on employee performance based on the latest literature review from 2020 to 2025. The method used is a systematic literature review by collecting and examining ten academic articles that meet the inclusion criteria from Google Scholar. The selected articles are evaluated based on their relevance and feasibility in supporting the research objectives. The analysis results show that effective leadership and positive organizational culture significantly contribute to improving employee performance, both directly and indirectly. These findings emphasize the important role of leaders and the organizational environment in driving productivity and achieving company goals.